TRANSFORMASI SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) MENJADI INSTITUT AGAMA ISLAM NEGERI (IAIN) DALAM MENINGKATKAN PELAYANAN AKADEMIK (Studi Persepsi Mahasiswa PGMI) - Zulkarnain; Ahmad Syukri; Maisah (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2021)
This study aims to describe the reasons for the transformation of STAIN into IAIN and pre-post-transformation academic services, as well as a study of PGMI students' perceptions of the transformation of the institution. The research background is IAIN Batusangkar and IAIN Bukittinggi in West Sumatra Province. This study uses a qualitative approach with analytical descriptive method. Determination of research subjects by snowball sampling, data analysis with data reduction techniques, data presentation, data verification and drawing conclusions. The results of this study indicate that (1) STAIN Batusangkar and STAIN Bukittinggi perform transformations influenced by internal and external factors; (2) The historical aspects of the two institutions with well-known campuses in West Sumatra, namely UIN Imam Bonjol and Padang State University (UNP); (3) efforts to increase the reach of equity, distribution of quality, and competitiveness in the era of globalization; (4) improvement of academic services includes graduate competence, content, process, assessment, lecturers (educators), infrastructure, management, and education financing. Thus, it is concluded that the transformation of STAIN into IAIN in West Sumatra can improve academic services.